Thrombosis in Children: Current Perspective and Distinct Challenges - Richardson, Matthew W.; Allen, Geoffrey A.; Monahan, Paul E. (Thrombosis and Haemostasis, 2002)
Coincident with a true increase in the incidence of thrombosis in childhood has come an appreciation of the impact of thromboembolic events upon children. In part, the greater awareness of childhood thrombosis reflects improved diagnostic imaging, which allows more sensitive identification of clots in infants and children. At the same time, advances in supportive care have meant that more children are being exposed to, surviving and living with thromboembolic risk factors and complications than previously. Because data regarding pediatric thrombosis have been lacking, treatment strategies have been extrapolated from experience in adults. This approach, however, results in diagnostic and therapeutic pitfalls. An understanding of issues unique to pediatric thrombosis is required; recent insights and the ongoing challenges are reviewed.Following the submission of this manuscript, the Subcommittee for Perinatal and Pediatric Thrombosis and of the Scientific and Standardization Committee of the International Society on Thrombosis and Haemostasis (ISTH) generated two relevant communications, published in the July, 2002 issue of Thrombosis and Haemostasis. While the positions communicated, entitled “Laboratory testing for thrombophilia in pediatric patients (117)” and “Recommendations for tPA thrombolysis in children (118)” do not conflict with this manuscript, they will be of interest to the reader.
Keywords: Thrombosis; child; neonate; hemostasis; anticoagulation; thrombophilia